USAHA PENINGKATAN KOMPETENSI SOFTSKILL MELALUI STUDENT CENTERED-LEARNING BAGI MAHASISWA YANG MENGIKUTI MATA KULIAH ANALISA PERANCANGAN SISTEM - Arief, Rifiana (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The face to face learning process focuses on teacher-centered learning (the center of the learning activity is on the teacher or lecturer – the students just notice and listen the lecturer's explanation), it is the reverse of student-centered learning (students' active participation). The changing of learning model from teacher-centered approach into student-learning center should be conducted to increase the students' active participation in System Design and Analysis course. The research methods to improve students' softskills competency through studentcentred learning were (a) making lecturer team who taught System Design and Analysis course (b) reviewing the syllabus of lecturing unit (c) developing a learning model of student learning center to maximize the students' hardskills and to stimulate their softskills (d) conducting socialization of new revised syllabus of lecturing unit that covered softskills competency, of which it had been validated by the university party (e) implementing the learning process with the student-learning center approach by using syllabus of System Design and Analysis which covered softskills competency. By implementing the model of student learning center on System Design and Analysis learning process, it was expected to be able to maximize the understanding of hardskills, technology for analysis and information system design as well as to stimulate the student's intrapersonal and interpersonal skills (softskills), who completed the course. Keywords: softskills competency, student-centred learning, System Design and Analysis,